Pemikiran Abu Yusuf tentang Pajak dan Relevansinya di Zaman Sekarang - Yola Aprilia Sibagariang; Hendra Hendra (Universitas Dian Nuswantoro, 2022)
Taxes are the largest source of state revenue. Government development and operational budgets have a large dependence on taxes. Tax implementation has existed since Prophet Muhammad SAW, tax implementation continues. During the Abbasid dynasty, there was a scholar named Abu Yusuf who wrote about taxation at the request of Amir Al-Mu'minin, Abu Yusuf was asked to prepare a comprehensive book that could be used as evidence of legal tax collection, which was compiled to avoid people's pressure. Abu Yusuf tends to expose diverse economic thought by using qiyas analysis and begins with an in-depth study of the Qur'an, the hadith of the prophet, atsar sahabi, and also the practices of the rulers. The basic idea is to realize al-maslahah al-ammah (public interest). This approach produces diverse, more relevant and consistent ideas. In the case of taxes, he has developed clear principles that in the coming centuries may be known to economists as rules of taxation.